2018
DOI: 10.1111/aogs.13362
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal risk factors associated with neonatal morbidity in large‐for‐gestational‐age infants: an international prospective cohort study

Abstract: Regular physical activity in mid-pregnancy is associated with lower risk for neonatal morbidity in large-for-gestational-age infants and seems to offer protection against the increased risk associated with higher maternal glucose levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Large-for-gestational-age (LGA), which is defined as a birth weight above the 90th centile, is associated with increased perinatal mortality and morbidity,1–3 future risk of developing obesity and insulin resistance 4–6. LGA increases the risk of shoulder dystocia and neonatal intensive care unit admission, and maternal risks include higher caesarean section rates, postpartum haemorrhage and third-degree and fourth-degree tears 7–9. Several studies have suggested that prenatal identification of LGA and appropriate management of delivery in suspected LGA infants are effective preventive measures to prevent delivery‐related perinatal morbidity 7 10.…”
Section: Introductionmentioning
confidence: 99%
“…Large-for-gestational-age (LGA), which is defined as a birth weight above the 90th centile, is associated with increased perinatal mortality and morbidity,1–3 future risk of developing obesity and insulin resistance 4–6. LGA increases the risk of shoulder dystocia and neonatal intensive care unit admission, and maternal risks include higher caesarean section rates, postpartum haemorrhage and third-degree and fourth-degree tears 7–9. Several studies have suggested that prenatal identification of LGA and appropriate management of delivery in suspected LGA infants are effective preventive measures to prevent delivery‐related perinatal morbidity 7 10.…”
Section: Introductionmentioning
confidence: 99%
“…Mothers of LGA or macrosomic (birthweight greater than 4.0–4.5 kg) babies are at higher risk of intrapartum complications (prolonged labour, assisted vaginal birth, emergency caesarean section, shoulder dystocia, perineal trauma and haemorrhage), and possibly stillbirth. The babies have greater risk of neonatal complications (low Apgar score, neonatal unit admission, neonatal trauma, transient tachypnoea, hyperbilirubinaemia or hypoglycaemia) 1–6 …”
Section: Introductionmentioning
confidence: 99%
“…The babies have greater risk of neonatal complications (low Apgar score, neonatal unit admission, neonatal trauma, transient tachypnoea, hyperbilirubinaemia or hypoglycaemia). [1][2][3][4][5][6] Unlike the universal screening programmes for fetuses that are small for gestational age (SGA), guidelines on antenatal care do not recommend routine screening for LGA. 7,8 Conversely, serial ultrasound fetal growth assessment is recommended for women with diabetes or with a body mass index (BMI) of ≥35.0 kg/m 2 in pregnancy, [9][10][11] both associated with LGA.…”
Section: Introductionmentioning
confidence: 99%
“…Maternal diabetes, uncontrolled diabetes, excessive weight gain during pregnancy, a history of macrosomia in a previous pregnancy, gestational diabetes mellitus (GD), obesity, excessive gestational weight gain, and postterm pregnancy are risk factors for infant macrosomia (6,7). Macrosomic children born to non-diabetic mothers may be at risk due to maternal obesity and genetics (7).…”
Section: Introducti̇on and Ai̇mmentioning
confidence: 99%